Haloargentinum marplatensis gen. nov., sp. nov., a novel extremely halophilic bacterium isolated from salted-ripened anchovy (Engraulis anchoita) - Perez, Silvina (2020)
A facultative aerobic, Gram-negative, motile, non-endospore forming and extremely halophilic bacterium, strain 11aii⊺, isolated from salted-ripened anchovy, was examined using a polyphasic approach to characterize and clarify its phylogenetic and taxonomic position. Sequences of the 16S rRNA gene revealed close relationships to species of the genera Lentibacillus and Virgibacillus (94.2% similarity). The organism grew optimally in the presence of 20-35 % NaCl. The major fatty acids of strain 11aii⊺ were C16:0 (42.1%) and anteiso-C15:0 (31.2%) and also presented iso-C16:0 (11.0%), anteiso-C17:0 (10.4%) and C18:0 (5.2%). Based on data presented here, strain 11aii⊺ is considered to represent a novel genus and species, for which the name Haloargentinum marplatensis gen. nov. sp. nov. is proposed with the strain 11aii⊺ as type strain.